’Een ploertendoder in een dierbaar en schoon gelaat’. Piet Zanstra’s nieuwe raadzaal voor Den Haag - van den Biggelaar, Jeroen (Bulletin KNOB, 2017)
In the 1960s and ’70s, the modernist architect Piet Zanstra was at the helm of one of the biggest and most productive architectural firms in the Netherlands. Although he and his firm were responsible for thousands of dwellings and apartments in new residential developments, the Maupoleum (1971) is his best-known design. This office colossus, located on the outskirts of Amsterdam’s city centre, was regularly dubbed the ugliest building in the city and even in the Netherlands. Inevitably, its reception coloured the portrayal of Zanstra in the literature, namely that he was unwilling to adapt his designs to the scale of the historical city and that he had little time for historical architecture. The new council chamber in The Hague (1972), one of Zanstra’s other, less well-known projects, appears to confirm this imputed attitude. Here he designed a modern annexe that in style and form, like the Maupoleum, was poorly integrated into the historical and small-scale urban surroundings. And again like the Maupoleum, this building was decried by local residents. There has been no previous research into the history of the council chamber design, even though it is a much better project by which to assess Zanstra’s attitude to the historical, small-scale city centre. My research has shown that the project had a long gestation, and that Zanstra was only involved in the plans for the new building at a later stage. It also transpires that the design was heavily influenced by radical modifications planned for the immediate area, which never came to fruition. And so the council chamber was never given the setting that would have shown it to best advantage. In addition, there seems to be little evidence to support the belief that Zanstra lacked empathy for the historical city and its architecture. On the contrary, he seems to have been very supportive of the restoration of the old town hall, and hoped to inject new vigour into the old and run-down city centre. When, two decades later, the city council moved into a new city hall on Spui, there appeared to be little enthusiasm for preserving Zaanstra’s council chamber. Like the Maupoleum, the council chamber did not get the context for which it was designed and, 25 years after completion, it was demolished.